2014
DOI: 10.1017/s0007114514000051
|View full text |Cite
|
Sign up to set email alerts
|

Micro-architectural changes in cancellous bone differ in female and male C57BL/6 mice with high-fat diet-induced low bone mineral density

Abstract: The relationship between fat and bone mass at distinct trabecular and cortical skeletal compartments in a high-fat diet (HFD) model was studied. For this, C57BL/6 mice were assigned to four groups of eight animals each. Two groups, each of males and females, received a standard chow diet while the remaining other two groups received the HFD for a period of 10 weeks. Male mice on the HFD were heavier and gained more weight (15·8 %; P, 0·05) v. those on the control diet or when compared with the female rats fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 46 publications
(60 reference statements)
9
75
1
Order By: Relevance
“…Transfections of the agomir and antagomir into mouse osteoblasts were carried out at 50 -60% confluence with reduced-serum and antibiotic-free OptiMEM using the transfection agent Lipofectamine (Invitrogen). Alp activity, mineralization, and qPCR were performed using protocols published previously (19,20). For the reporterpromoter assays, Runx2-Luc and Renilla luciferase vectors (from GeneCopoeia) were co-transfected into osteoblasts, and luciferase activity was determined using a dual assay luciferase kit (19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfections of the agomir and antagomir into mouse osteoblasts were carried out at 50 -60% confluence with reduced-serum and antibiotic-free OptiMEM using the transfection agent Lipofectamine (Invitrogen). Alp activity, mineralization, and qPCR were performed using protocols published previously (19,20). For the reporterpromoter assays, Runx2-Luc and Renilla luciferase vectors (from GeneCopoeia) were co-transfected into osteoblasts, and luciferase activity was determined using a dual assay luciferase kit (19).…”
Section: Methodsmentioning
confidence: 99%
“…Alp activity, mineralization, and qPCR were performed using protocols published previously (19,20). For the reporterpromoter assays, Runx2-Luc and Renilla luciferase vectors (from GeneCopoeia) were co-transfected into osteoblasts, and luciferase activity was determined using a dual assay luciferase kit (19). The full length of the Runx2 promoter is 1039 bp (catalog no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,8,10] In contrast, a combined high-fat/sucrose diet impairs lumbar and femoral neck strength in rodents, likely a result of smaller bone cross-sectional area and/or reduced cortical bone area in comparison to a low-fat/complex carbohydrate diet. [37, 51] Interestingly, we observed that the cortical bone compartments at the distal femur and femoral diaphysis of HF and HF/F animals exhibited increased Ct.Th and Ct.Ar/Tt.Ar and densitometric characteristics, although, these changes did not improve whole bone mechanical characteristics in comparison with Controls.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…[4] Similarly, high-fat [5][6][7][8][9][10] or high fructose diets [11,12] [20] suggesting that increased oxidative stress resulting from ROS generation and/or reduced activity of the antioxidant systems may influence the adverse skeletal development resulting from high-fat or high-fructose diets.…”
Section: Introductionmentioning
confidence: 99%